Successful Treatment of Bullous Pemphigoid Lesions by Berberine Stamp Therapy: A Case Report and Literature Review - Cheng, Linyan; Wang, Yi; Lu, Hanzhi; Guo, Wanjun; Yan, Ge; Zhu, Jianyong; Guo, Dongjie; Li, Fulun (Frontiers in Medicine, 2022)
Bullous pemphigoid (BP) is a life-threatening autoimmune disease of the skin, which is mainly characterized by large areas of tonic blisters and intense itching of the skin. The one-year mortality rate of BP was 23.5%. Superinfection caused by skin lesion ulceration is one of the important causes of disease death. Therefore, it is a challenge to control infection and improve skin wound healing. Here, we report the case of an elderly woman who presented with BP and involved the oral mucosa. The patient was successfully treated with hormones combined with topical berberine and 95% of the patients' lesions healed completely after one month. In addition, we inductively analyzed the current treatments for BP, so as to provide a reference for the clinical treatment of BP.